Perlindungan Hukum Terhadap Korban Tindak Pidana Dalam Perspektif Viktimologi Di Indonesia - Muhammad Fajar Lutfi Raihan; Amos Saito Hamonangan Simorangkir; Adil Abdillah; Dhaffa Hosya Putra; Ria Anggraeni Utami (GLOBAL SCIENTS PUBLISHER, 2026)
This research comprehensively examines the legal protection afforded to crime victims within the framework of victimology in Indonesia. For decades, the Indonesian criminal justice system has tended to prioritize perpetrators over victims, leaving the latter's interests inadequately addressed. Employing a normative juridical approach supplemented by conceptual analysis, this study identifies that while Indonesia's legal framework for victim protection particularly Law No. 13 of 2006 as amended by Law No. 31 of 2014 on the Protection of Witnesses and Victims has made considerable progress, significant systemic gaps persist. Applying a critical victimology lens, this study finds that the implementation of victim rights such as restitution, compensation, and rehabilitative assistance remains suboptimal due to weak enforcement mechanisms, limited institutional capacity of LPSK (Witness and Victim Protection Agency), and insufficient victim access to legal information. This research concludes that reforming the victim protection system requires a more holistic approach not merely normative but also structural and cultural to ensure that victims can substantively enjoy their legally guaranteed rights.